Improving adolescents’ HIV/AIDS prevention behavior: A phenomenological study of the experience of planning generation program (GenRe) ambassadors as peer educators - Diah Ratnawati; Agus Setiawan; Junaiti Sahar; Widyatuti; Astuti Yuni Nursasi; Tatiana Siregar (Belitung Nursing Journal, 2024)
Background: Adolescents face increased vulnerability to HIV/AIDS due to factors such as insufficient knowledge and awareness, stigma, and restricted access to information. The Indonesian government initiated a peer education program through the Planning Generation Program (GenRe) ambassadors. These ambassadors are tasked with educating their peers about HIV/AIDS. However, their experiences are largely underexplored. Objective: This study aimed to explore the GenRe ambassadors’ experience in improving adolescents’ HIV/AIDS prevention behavior. Methods: This study employed a qualitative phenomenological approach, with in-depth and semi-structured interviews of GenRe ambassadors who had served for at least three to six months within the South Jakarta Health Sub-Department, Indonesia. Purposive sampling and data saturation techniques were utilized. Data were collected from 13 May to 31 August 2022, and Colaizzi’s steps were used to guide the data analysis. Results: Nineteen GenRe ambassadors participated, predominantly female university students ages 18–22. Six themes were developed: 1) the impact of GenRe ambassadors’ roles in improving HIV/AIDS prevention behavior, 2) activities to improve HIV/AIDS prevention behavior, 3) enhancement of self-concept as GenRe ambassadors, 4) obstacles to activities for improving HIV/AIDS prevention behavior, 5) support for activities to improve HIV/AIDS prevention behavior, and 6) hope for improving the GenRe ambassador program’s implementation. Conclusion: GenRe ambassadors are influencers who play a critical role in promoting HIV/AIDS prevention behaviors and fostering positive change in the broader youth community. Despite their positive self-concept, they encounter challenges in fulfilling their roles. Utilizing their insights, community health nurses can create effective peer-led HIV/AIDS prevention programs and contribute to a model of health promotion for adolescents. Leveraging the role of GenRe ambassadors as peer educators is recommended to enhance HIV/AIDS prevention efforts among adolescents.